PERILAKU SPORTIVITAS DAN FAIRPLAY OLAHRAGA - Rachmi Marsheilla Aguss; Eko Bagus Fahrizqi; Fedi Ameraldo; Reza Adhi Nugroho; Imam Mahfud (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2022)
Fair play is a mental attitude that shows the dignity of chivalry in sports. The value of fair play underlies the formation of attitudes, and then attitudes become the basis of behavior. So it can be concluded that fair play provides equal chances of winning for both teams. This type of research is descriptive research research not intended to test certain hypotheses, but only describes "what is" about a variable, symptom or situation". The data collected in this study is data in the form of numbers, so this research is called descriptive quantitative research. Its standard deviation is 5,536. The minimum score is 55 and the maximum score is 80. The scoring norms are presented in the following table: low 0% From these results it can be concluded that students of SMAN 1 Rajabasa have a high sportsmanship attitude, therefore they always instill a sportsman spirit. This is shown during training by following a patterned training system, training discipline, practicing spirit, obeying the rules, and having a sense of tolerance and respect for friends and playing opponents, so that the category of very high level of sportsmanship is in SMAN 1 Rajabasa students..